Turnover intention of information technology professionals in Sri Lanka: The influence of perceived organizational support, professional commitment and job satisfaction / Mohamed Buhari Mufitha - Mohamed Buhari , Mufitha (2019)
Information technology (IT) industry is one of the top four industries with low employee retention rate. Considering the high cost involved in replacements, companies are keen to know what will keep IT professionals with their organizations. Anchored in social capital and social exchange theories, this study investigated the influence of perceived organizational support and professional commitment on IT professionals’ turnover intentions. A partial least square structural equation model (PLS-SEM) analysis of 383 software engineers from Sri Lanka revealed that both perceived organizational support and professional commitment weaken turnover intentions and job satisfaction partially mediates such relationships. Nevertheless, comparing between the two predictors, professional commitment found to be the stronger predictor of turnover intentions than perceived organizational support. Further, the results suggested that perceived organizational support and professional commitment are positive stimulus to increase job satisfaction. It is concluded that (1) when reached to mature career stages, IT professionals’ intentions to leave the current organization decrease, (2) gender has no effect in their turnover intentions, and (3) co-workers, supervision, and work design are the most influencing job satisfaction factors. Among factors of perceived organizational support, job satisfaction-related support was the most sought form of support. The findings suggest that IT firms might concentrate on professional advancement, job designing, and supervision in their retention strategies. Some stereotypes related to IT professionals were challenged from the behaviour of professional commitment component and from the zero effect of gender in the model. Theoretically, the study contributes to better understand IT professionals’ turnover behaviours, and to widen the applications of social capital and social exchange theories in turnover models. It also strengthens the argument that professional commitment is more relevant than continuous organizational commitment in knowledge workers’ turnover studies.